(untitled) (Journal of the College of Basic Education, 2022)
The study aims to: 1-Building a measure of the cognitive and technical adequacy of football coaches of the education directorates in Baghdad. 2- Identifying the cognitive and technical competences that must be available to football coaches in Baghdad education directorates The researcher used the descriptive method in the style of survey studies to suit the problem of research. The researcher chose the sample in the deliberate way as it represents the elite of the research community and the researcher chose the entire research community as (6) education directorates were selected representing (3) educations belonging to the karkh cutter and (3) educations of the al-Rasafa cutter and the number of football coaches For these educations (124) trainers were excluded and (20) trainers representing the reconnaissance experience were excluded (4) coaches due to the lack of filling of the questionnaire and thus the number of sample members (100) became trainers as installed in the official data of these sensors. To achieve the first goal of the research, which is to build a measure of the cognitive and technical competences of football coaches, the researcher has followed specific steps, namely identifying the areas of the scale, drafting paragraphs for each area, and then applying these paragraphs to a sample representing the community, and then conducting statistical analysis of the paragraphs to choose the appropriate paragraphs to measure the phenomenon to be measured. The process of building a measure of cognitive and technical competences has passed through a set of procedures that the researcher applied After presenting and discussing the results of the research, the researcher reached a number of conclusions, which are as follows: 1- It was reached to build a measure of the cognitive and technical competences of football coaches. 2- Based on the results of the statistical analysis, (6) areas were drawn, representing the measure of the cognitive and technical competences of football coaches with (41) paragraphs as follows. A- The first area contained (7) paragraphs and called it the field of personal competences, B- The second area contained (7) paragraphs and called it the field of professional competences C-Field III contained (6) paragraphs and called it the field of training efficiency D- The fourth field contained (7) paragraphs and called it the field of scientific competences E- The fifth area contained (7) paragraphs and called it the field of cognitive competences The sixth area contained (7) paragraphs and was called the field of social competence.